2015
DOI: 10.1016/j.ijgo.2015.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression after failure of assisted reproductive treatment among patients experiencing infertility

Abstract: Patients with infertility have increased depression and anxiety after infertility treatment failure. Counseling or treatment for these potential psychological effects should be considered after infertility treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 24 publications
15
90
0
4
Order By: Relevance
“…It has many psychological effects as depression, anxiety, social isolation and deprivation, marital instability, loss of selfesteem and self-confidence, loss of gender identity, loss of control, and feeling of self-blame and guilt that subsequently lead to low quality of life. (40,41) This present study result is supported by Maroufizadeh S et al (2017) (42) who found that the total core quality of life was 62.6±16.9, and the total treatment quality of life was 58.4±12.9, which indicated that the women had the lowest overall quality of life. In addition, this finding is also in agreement with the results of another study done by Masoumi S et al (2016).…”
Section: Coping Strategies and Quality Of Life Among Infertile Women supporting
confidence: 85%
“…It has many psychological effects as depression, anxiety, social isolation and deprivation, marital instability, loss of selfesteem and self-confidence, loss of gender identity, loss of control, and feeling of self-blame and guilt that subsequently lead to low quality of life. (40,41) This present study result is supported by Maroufizadeh S et al (2017) (42) who found that the total core quality of life was 62.6±16.9, and the total treatment quality of life was 58.4±12.9, which indicated that the women had the lowest overall quality of life. In addition, this finding is also in agreement with the results of another study done by Masoumi S et al (2016).…”
Section: Coping Strategies and Quality Of Life Among Infertile Women supporting
confidence: 85%
“…Undeniably, infertility causes lots of distressing and anxious experiences such as loss of self-esteem, depression, frustration, emotional and sexual distress and marital problems (16-20). Lawson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Respecto al peso, se observa un promedio de 64,93 kg (DE ± 9,46), solo el 32,5 % (n = 13) tenía en peso normal, un 2,5 % (n = 1) estaba con bajo peso, un 52,5 % (n = 21) tenía sobrepeso y un 12,5 % (n = 5) eran obesas. Se observó un índice de masa corporal (IMC) promedio de 25,94 (DE ± ,35).…”
Section: Resultsunclassified
“…Respecto a las condiciones de salud mental se pudo observar que la ansiedad severa estuvo presente en cifras similares a las encontradas en el estudio realizado en Irán en 208 mujeres infértiles, quienes en el 45,8 % de los casos presentaron altos niveles de depresión y de ansiedad (35). Por otro lado, un estudio realizado en población noruega, publicado a principios del año 2015, en 12.584 mujeres entre 19 y 45 años, mostró que el 40 % de estas mujeres presentan niveles de ansiedad severa, y el 60 % presenta cifras de desesperanza elevada (36).…”
Section: Discussionunclassified